فيديوهات البث المباشر عبر المنصات الاجتماعية و علاقتها بتشكيل اهتمامات المراة اتجاه نمط الحياة اليومية - نويوة فتيحة; زبيدة يمنمى كامل; د/ احمد قسمية (جامعة عمار ثليجي بالاغواط, 2025)
ملخص تناولت هذه الدراسة موضوع فيديوهات البث المباشر عبر المنصات الاجتماعية و علاقاتها بتشكيل اهتمامات المراءة اتجاه نمط الحياة اليومية ممثلا موظفات كلية العلوم الإنسانية بجامعة عمار ثليجي الاغواط قد كان الهدف من هذه الدراسة التعرف على سبب فيديوهات البث المباشر عبر المنصات الاجتماعية و علاقتها بتشكيل اهتمامات المراة اتجاه نمط الحياة اليومية و ما نوع المضامين التي تتابعها المرءة عبر الانستغرام واما اذ ما كانت تابع صفحات الميكب ارتيست و هدفها من متابعة هذه الصفحات و قد اعتمدنا على هذه الدراسة المنهج الوصفي التحليلي و العينة القصدية من المجتمع البحث المتمثل في نساء من موظفات كلية العلوم الإنسانية بجامعة عمار ثليجي الاغواط و اعتمدنا على الاستبيان كاداة لجمع المعلومات و قد تضمنت على بالكلية و بعد جمع و التحليل البيانات توصلنا الى مجموعة من النتائج أهمها : توصلنا ان اغلب العينة ان تصفحهن للبثوث المباشرة هو للتسلية و الترفيه و أيضا متابعة كل ما هوجديد حول عالم الميكب ارتيست وهن يستفيدن من النصائح و الارشادات التي تقدمها المؤثرات عبر فيدديوهات البث المباشر في الانستغرام و تصفح صفحات الميكب ارتيست هولتحقق لهن سعادتهن الشخصية و لكسب مكانة في المجتمع و استعمال ماركة الميكب ارتيست هو لجودة منتجاتها الكلمات المفتاحية : مواقع التواصل الاجتماعي ، فيديوهات البث المباشر ، انستغرام Summary : This study addressed the topic of live streaming videos on social media platforms and their relationship to shaping women's interests in daily lifestyle patterns, with a focus on female employees at the Faculty of Humanities, Amar Telidji University of Laghouat. The aim of this study was to understand the reasons behind women’s engagement with live streaming videos on social media platforms and how these videos influence their interests regarding daily lifestyle choices. The study also explored the types of content women follow on Instagram, specifically whether they follow makeup artist pages, their motivations for doing so, and the impact of such content. This research adopted a descriptive-analytical methodology and a purposive sample from the research population, which consisted of female employees at the Faculty of Humanities at Amar Telidji University of Laghouat. A questionnaire was used as the main data collection tool, comprising 24 questions divided into three axes. A total of 60 forms were distributed among a sample of female employees at the faculty. After collecting and analyzing the data, the study reached several key findings, most notably: The majority of the sample browse live streams mainly for entertainment and leisure purposes, as well as to keep up with the latest trends in the world of makeup artists. They also benefit from the advice and guidance provided by influencers through live streaming videos on Instagram. Following makeup artist pages contributes to their personal happiness and helps them gain social status. They also choose to use products from makeup artist brands due to the perceived quality of these products. Keywords: Social media platforms, live streaming videos, Instagram.
دراسة ميدانيةلعينة من موظفات لكلية العلوم الانسانية متابعات انستغرام